Mengembangkan Kepercayaan Diri Berinteraksi Sosial Melalui Pendekatan Cognitive Behavior Therapy Teknik Cognitive Restructuring pada Siswa Sma Negeri 2 Bae Kudus - Mahardika Putra Pratama; Edris Zamroni; Gudnanto Gudnanto (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
This study aims to develop social interaction confidence through cognitive behavior therapy using cognitive restructuring techniques in students at SMA Negeri 2 Bae Kudus. The background of this study is based on the phenomenon and reality that students often show a lack of confidence (introversion) in their environment, especially in social interactions at school. The objectives of this study are: (1) To identify the factors that influence a lack of confidence in social interaction. (2) To identify the development of confidence in social interaction using the cognitive behavior therapy technique of cognitive restructuring. The treatment used was Cognitive Behavior Therapy counseling with Cognitive Restructuring techniques. This study used a qualitative approach with a case study design. The subjects were students at Bae Kudus 2 Public High School who appeared to lack confidence (introverts) in social interactions at school. The data collection techniques used were observation, documentation, and in-depth interviews to obtain valid data in accordance with what occurred in the field.The results of the study show that AP has succeeded in gradually changing his mindset and behavior in a meaningful way. From someone who was previously passive, easily anxious, nervous, and lacking in confidence, AP has now developed into a confident, more self-aware, more proactive individual who has healthier strategies for dealing with various social situations. The conclusion of this study is that the factors causing AP to have problems within himself and the application of Cognitive Behavior Therapy counseling techniques of Cognitive Restructuring in developing the social interaction confidence of students at SMAN 2 Bae Kudus can be implemented, which shows that the Cognitive Behavior Therapy counseling approach using Cognitive Restructuring techniques has been proven effective and has experienced a significant increase in the serious handling of confidence in social interaction.